2020
DOI: 10.1371/journal.pmed.1003374
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Epidemiological Analysis of Comorbidities and Treatments as risk factors for COVID-19 in Scotland (REACT-SCOT): A population-based case-control study

Abstract: Background The objectives of this study were to identify risk factors for severe coronavirus disease 2019 (COVID-19) and to lay the basis for risk stratification based on demographic data and health records. Methods and findings The design was a matched case-control study. Severe COVID-19 was defined as either a positive nucleic acid test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the national database followed by entry to a critical care unit or death within 28 days or a death certifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 12 publications
1
106
1
1
Order By: Relevance
“… 26 In the English National Audit cohort, 13 , 14 the risk ratio of COVID-19 death for type 1 diabetes was 3·51 and for type 2 it was 2·03; these were attenuated in White people (3·06 for type 1 and 1·91 for type 2). In a matched case control study 27 of the total population of Scotland from earlier in the pandemic and not including cases derived solely from hospital admissions (which were not yet available), we reported slightly higher conditional ORs of 2·75 (95% CI 1·96–3·88) for type 1 diabetes and 1·60 (1·48–1·74) for type 2 diabetes. All these studies are therefore consistent in finding elevations in risk for type 1 and type 2 diabetes in the same range.…”
Section: Discussionmentioning
confidence: 75%
“… 26 In the English National Audit cohort, 13 , 14 the risk ratio of COVID-19 death for type 1 diabetes was 3·51 and for type 2 it was 2·03; these were attenuated in White people (3·06 for type 1 and 1·91 for type 2). In a matched case control study 27 of the total population of Scotland from earlier in the pandemic and not including cases derived solely from hospital admissions (which were not yet available), we reported slightly higher conditional ORs of 2·75 (95% CI 1·96–3·88) for type 1 diabetes and 1·60 (1·48–1·74) for type 2 diabetes. All these studies are therefore consistent in finding elevations in risk for type 1 and type 2 diabetes in the same range.…”
Section: Discussionmentioning
confidence: 75%
“…Across the entire Scottish population, 6346 hospital admissions with covid-19 occurred (table 2 and supplementary figure B). REACT-COVID-19 included clinical data on all these cases and 10 randomly selected controls for each case (supplementary figure B) 10. Of 6346 hospital admissions with covid-19 in Scotland, 33% (n=2097) occurred in the working age population (18-65 years).…”
Section: Resultsmentioning
confidence: 99%
“…In the case-control study, we did conditional logistic regression. As REACT-COVID-19 used incidence density sampling,10 the effect measure estimates derived from these case-control analysis are directly comparable to those derived from the Cox regression. To allow comparison against the general population across the cohort and case-control analyses, we used the non-patient facing role as a common reference group.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In initial analysis of a matched case-control study of risk factors for severe COVID-19 in Scotland (REACT-SCOT), we reported a strong association of severe COVID-19 with dispensing of at least one prescription in the past year [ 3 ]. The univariate rate ratios associated with at least one prescription varied from 3.8 in those aged under 60 years to 2.3 in those aged 75 years and over.…”
Section: Introductionmentioning
confidence: 99%